2011
DOI: 10.1007/s11695-011-0455-5
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric Surgery Pharmacy Consultation Service

Abstract: Bariatric surgical patients often need changes in formulation and dosages of their medications. The literature contains minimal information regarding pharmaceutical care and consultation services for the bariatric surgery patient. Complex medication regimens and safety concerns initiated a collaborative effort between surgeons and pharmacists to manage more effectively bariatric patients perioperatively. The consultation service included patient identification, pharmacy referral, pharmacist consultation with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 2 publications
(4 reference statements)
0
17
1
Order By: Relevance
“…When discharged from the hospital, patients should be carefully instructed on the modifications of their medication regimen, including changes in prescription drugs, over-the-counter drugs, nutrient supplements and homeopathic drugs. Involvement of pharmacists as advisors in the drug treatment is beneficial for both surgeons and patients [80]. If possible, oral liquid-dosage forms should be used instead of solid-dosage forms for at least 2 months after surgery.…”
Section: Pharmacotherapy After Bariatric Surgerymentioning
confidence: 99%
“…When discharged from the hospital, patients should be carefully instructed on the modifications of their medication regimen, including changes in prescription drugs, over-the-counter drugs, nutrient supplements and homeopathic drugs. Involvement of pharmacists as advisors in the drug treatment is beneficial for both surgeons and patients [80]. If possible, oral liquid-dosage forms should be used instead of solid-dosage forms for at least 2 months after surgery.…”
Section: Pharmacotherapy After Bariatric Surgerymentioning
confidence: 99%
“…12,13 Pharmacists have a unique opportunity to increase patient safety in bariatric surgery in the immediate postoperative period. Pharmacists can assist surgeons by performing medication reconciliation and patient interviews.…”
Section: Hypertension and Diabetes Mellitus Medication Management In mentioning
confidence: 99%
“…Silverman et al [30] performed 124 consultation services for bariatric surgery patients from February 2, 2009 to December 1, 2010. Their services included patient identification, pharmacy referral, pharmacist consultation with the patient, communication of recommendations with surgeons, follow-up and documentation.…”
Section: Discussionmentioning
confidence: 99%
“…Their services included patient identification, pharmacy referral, pharmacist consultation with the patient, communication of recommendations with surgeons, follow-up and documentation. They concluded that the collaborative effort between surgeons and pharmacists effected changes in medication transitioning perioperatively and resulted in improved pharmaceutical care for this patient population [30]. Such services might improve patient compliance with medications; however the literature contains minimal information regarding pharmaceutical care and consultation services for the bariatric surgery patient and to our knowledge their effect on compliance rates has not been adequately addressed.…”
Section: Discussionmentioning
confidence: 99%